Impaired Mood in Headache Clinic Patients: Associations With the Perceived Hindrance and Attainability of Personal Goals. Issue 6 (20th May 2016) - Ciere, Yvette; Visser, Annemieke; Lebbink, John; Sanderman, Robbert; Fleer, Joke
Abstract : Background: Headache disorders are often accompanied by impaired mood, especially in the headache clinic population. There is a large body of literature demonstrating that an illness or disability may affect the way in which patients perceive their personal goals and that the perception that the attainability of goals is hindered by the illness is a risk factor for impaired mood. However, empirical evidence regarding the extent to which goals are hindered or less attainable as a result of a headache disorder, and how that is related to mood, is currently lacking. Objective: The aim of this cross‐sectional study was to examine associations between headache severity, goal hindrance and attainability, and mood in a headache clinic population. Methods: The sample consisted of 65 adult patients seeking treatment at a tertiary headache clinic. Prior to their first appointment in the clinic, patients completed self‐report measures of headache severity, goals and mood (PANAS). Results: Higher self‐reported headache intensity was associated with higher goal hindrance (r = .38, P = .004), whereas greater headache frequency was associated with lower goal attainability (r = .30, P = .022). Higher perceived goal hindrance was associated with lower positive mood (r = −.27, P = .032) and higher negative mood (r = .28, P = .027). Furthermore, lower perceived goal attainability was associated with higher negative mood (r = −.34, P = .007). Goal perceptions explained an additional 11.4% of the variance in positive mood (F = 3.250, P = .047 <.05) and 10.5% of the variance in negative mood (F = 3.459, P = .039) beyond the effect of age and headache severity. Conclusion: The results of this preliminary study suggest that perceptions of increased goal hindrance and decreased goal attainability may indeed be a risk factor for impaired mood in the headache clinic population and highlight the need for further, longitudinal research. Obtaining more insight into goal processes (eg, what types of goals are specifically disturbed, which goal adjustment strategies are (mal)adaptive) may help to identify ways to improve outcomes in the headache clinic population.